Progressive failure analysis for thin-walled composite beams under fatigue loads. (15th October 2016) - Rivera, Juan A.; Aguilar, Enrique; Cárdenas, Diego; Elizalde, Hugo; Probst, Oliver
Abstract: A thin-walled beam (TWB) model for integrated progressive failure analysis in composite materials under fatigue loading is presented for the first time. The model is computationally lean and capable of tracking the spatial distribution and further propagation of fatigue-induced damage in beam-like thin-walled composite structures (TWCS) by accounting for both sudden and gradual degradation of strength and stiffness moduli of material cells located at arbitrary positions. An integrated TWB model of a cylindrical symmetrical 8-layer test structure was studied to obtain insights into damage progression patterns and interactions between different damage mechanisms. It was shown that it is possible to localize and quantify the extent of damage at individual layers while providing explanations for damage initiation and propagation in engineering terms. The proposed model provides a computationally efficient platform for performing fatigue-induced progressive failure analysis in TWCS such as rotating blades of wind turbines or helicopters, allowing the assessment of a number of what-if scenarios with current off-the-shelve computing power.